Acute Chagas Disease: An epidemiological survey between 2012-2021 in the state of Piauí in Brazil (Research, Society and Development, 2024)
The objective was to understand the clinical-epidemiological profile of confirmed cases of Acute Chagas Disease (ACD) in the state of Piauí, from 2012 to 2021. An epidemiological, descriptive and retrospective study was carried out, with a quantitative approach, from 2012 to 2021. confirmed cases of ACD in the state of Piauí. Four cases of ACD were reported, with an increase in the number of notifications in 2021, with the municipality of Oeiras having the highest number of confirmed reported cases (75%), with a higher incidence of probable infection through the vector mode with laboratory confirmation criteria and good clinical evolution. The main age group affected was between 65-69 years old (50%), mixed race was the only one reported and there was no variation between the sexes. It is essential to know concise epidemiological data from the state of Piauí to improve medical care, prevention and control of Chagas Disease. Thus, the study initially allowed us to understand the socio-epidemiological profile of the state in relation to ACD, but it guides actions to improve the clinical diagnosis of ACD and correctly complete the Compulsory Notification Form so that future research can provide support for new implementations in public health in the state.